Vessel stability in polar low situations. (13th March 2017) - Orimolade, Adekunle Peter; Gudmestad, Ove Tobias; Wold, Lise Eide
ABSTRACT: An average of 12 polar lows develop yearly in the Norwegian and Barents Seas, when unstable air is accumulating over the ice–open water interphase. Polar lows are intense and rapid, accompanied by high wind speeds, large wave growth, and large snowfalls. There are uncertainties in polar low forecasts, and marine activities should not take place along the possible tracks of such events, even if the waves would be less than the extreme waves for the area. The metocean (meteorology and oceanography) conditions in polar lows suggest that a vessel at sea may experience severe sea spray icing. In this paper, we present vessel stability concerns, and the effect of snow and ice loads on stability, in polar low situations. Stability analysis results show that the additional snow and ice loads have more influence on smaller vessels' stability compared to larger vessels.